2006
DOI: 10.1074/jbc.m509036200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Transactivation Function of the Aryl Hydrocarbon Receptor by the Epstein-Barr Virus-encoded EBNA-3 Protein

Abstract: EBNA-3 is one of the Epstein-Barr virus (EBV)-encoded nuclear antigens that is indispensable for immunoblastic transformationand sustained proliferation of B-lymphocytes. The molecular mechanisms responsible for the function of EBNA-3 are poorly understood. We previously found that EBNA-3 interacts with an immunophilin-like protein XAP2/ARA9/AIP, which in mammalian cells is known to interact with the latent aryl hydrocarbon receptor (AhR). AhR is a ligand-inducible transcription factor that mediates cellular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 34 publications
0
36
0
1
Order By: Relevance
“…The overexpression of EBNA-3 induces G 0 /G 1 arrest (54), and the elimination of EBNA-3 results in cell death (55) in lymphoblastoid cell lines. EBNA-3 directly interacts with AhR and enhances its transactivational function via the ligand-activated AhR (56). TCDD-activated AhR induces cell cycle arrest at G 1 , accompanied by the increased expression of the CDK2 inhibitor p27 kip1 (57).…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of EBNA-3 induces G 0 /G 1 arrest (54), and the elimination of EBNA-3 results in cell death (55) in lymphoblastoid cell lines. EBNA-3 directly interacts with AhR and enhances its transactivational function via the ligand-activated AhR (56). TCDD-activated AhR induces cell cycle arrest at G 1 , accompanied by the increased expression of the CDK2 inhibitor p27 kip1 (57).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to premature degeneration of the thymus caused by the action of activated AhR in the earliest stages of life, [69][70][71] there is further preclinical evidence to support this concern, such as an affinity with Epstein-Barr virus in determining Hodgkin's lymphoma [84][85][86][87] and modulation of the BRCA-1 gene for breast cancer. 98 The 2% annual increase in the incidence of childhood tumors registered over the last 10 years in Italy, the increase in leukemias, lymph omas, and sarcomas in young people/adults, and the 1% increase in the incidence of breast cancers in the age group <45 years (1998-2005) may be related to the abovementioned mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In one, it was shown by a co-immunoadsorption assay, that the PPIase-like domain of AIP does not bind, or binds only very weakly, the cytoplasmic dynein (Galigniana et al 2002). In another study, it was demonstrated that the well-documented AIP-mediated cytoplasmic retention of the AhR (Kazlauskas et al 2000, 2002, LaPres et al 2000, Kashuba et al 2006 involves the anchoring of the complex to actin filaments (Berg & Pongratz 2002). By co-IP experiments, this interaction was proved to involve a direct binding of AIP to actin and also to take place only in the non-activated AhR complex, because TCDD treatment induces the release of the complex from actin (Berg & Pongratz 2002).…”
Section: Cytoskeletal Proteinsmentioning
confidence: 98%
“…This hypothesis was further supported by a following demonstration from the same group that besides AIP, EBNA-3 can also directly interact with the AhR, with AIP enhancing the stability of the complex. As a result of this association, an enhanced transcription of AhR-responsive genes has been observed (Kashuba et al 2006). …”
Section: Viral Proteinsmentioning
confidence: 99%